Robots stand on own two feet. - Riezenman, M.J.
Honda, Sony and Fujitsu are selling the first strolling humanoids. Honda's 120-cm-high Asimo is the tallest robot to amble admirably - not only on level ground, but up and down stairs and along slopes as well. To meet the challenge more easily, the latest robots scale things down: Fujitstu's new Humanoid for Open Architecture Platform (HOAP-1) is just 48 cm tall, while Sony's vaudevillian SDR-4X, the singer and dancer, is 58 cm.
Keywords: Fujitstu HOAP-1 robot; Honda Asimo robot; Humanoid for Open Architecture Platform; Sony SDR-4X robot; Robot height; Singing dancing robot; Two-legged locomotion; Walking humanoid robots